Membangun Kembali Spiritualitas Generasi Milenial: Relevansi Zuhud dalam Kitab Minhaj al-Abidin - Hamidi, Ali (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
The millennial generation tends to feel free from religious control and metaphysical views, thus viewing modern life as something temporary and instantaneous. This is often accompanied by individualistic, hedonistic, and wasteful attitudes and wastes of wealth and time. This kind of mindset pushes people away from the core of religious understanding, which ultimately leads to a spiritual vacuum. To overcome this problem, the proposed solution is to return to religion through the deepening of Sufism, especially by adopting zuhud behavior. This research aims to analyze the book Minhaj al-Abidin by Imam Al-Ghazali, especially in the chapter that discusses zuhud, as an effort to solve the spiritual problems of the millennial generation. This research is a library research, where data is collected through a review of books, scientific reports, and other scientific works. The data collection method used is documentation, namely by studying and interpreting literature according to the context. The results of this study reveal four main points. First, zuhud as a lifestyle for the millennial generation. Second, zuhud as a life motivation for the millennial generation. Third, zuhud as a solution to the spiritual problems of the millennial generation. Fourth, zuhud behavior is practiced by the students of the Baiturrahman Islamic Boarding School in Semarang Regency, Central Java. From these findings, the author argues that zuhud behavior can be a relevant lifestyle, a source of life motivation, and a solution to the spiritual crisis faced by this generation